Structure Behavior Analysis with Time History Levelling Method (Case Study in Building E ITERA) - A. Yudi; N. B. Wirawan; S. A. Fauzan; R. Nadeak (Journal of Science and Applicative Technology, 2019)
Mitigation of structural failure can be based on analyzing the behavioral of the structure by giving a nonlinear dynamic earthquake load of time history. Because Indonesia doesn’t have any data of time history record, it is necessary to match the time history data with the design spectrum response. Gedung E Itera is modeled on reinforced concrete structures with open frame models like as built drawing. Then can be evaluated the structural behavior that is like mass participation, plastic design, displacement, rotation, and base shear with time history load that will be levelling (levelling time history). With levelling the time history load , it can be found the first structural part that collapses and the maximum load that can be retained by the structure for one of the mitigation effort. The analysis uses a nonlinear dynamic time history analysis with the most dominant combination is earthquake combination. The results of this study show structural performance, the location of structural failure, and the maximum load that can be retained by the reinforced concrete structure of gedung E Itera.